Influence of UI Design Elements to a User-Friendly Learning Experience for Vocational School Students Department of DKV - Afrilya Puji Prayoga; Irfansyah Irfansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Over time, e-learning mobile applications were found, one of which was Skill Academy, which began to pay attention to the arrangement of its user interface (UI) design. The Skill Academy e-learning mobile application is suitable for supporting mastery of skills because there are materials that match the learning needs of SMK students in the Visual Communication Design department. The role of structuring UI design elements in e-learning mobile applications is important because it can be a means to build interest in learning to completion for students. Interest in learning arises because users feel that the UI design on learning media has met the user-friendly rules. A well laid out UI design will certainly give a different impression when compared to a makeshift one. Now the presence of the application which has begun to pay attention to the arrangement of the UI design display is the background for writing this research. The purpose of this study was to determine the effect of structuring UI design elements on a user-friendly learning experience for its users. The method used is the mixed method method. The quantitative method uses experimental tests in the form of data analysis from questionnaires compiled from UI design theory and UEQ+, with respondents being students majoring in Visual Communication Design at SMKN Purwosari Bojonegoro. While the qualitative method is a theoretical study of UI and usability. The result of the research is that the UI design has a significant effect on the user-friendly learning experience. As for UI design elements, only typography and image elements have a significant effect compared to other elements.